Predicting product demand from small-sized data: grey models. Issue 1 (6th February 2017) - Özdemir, Asli; Özdagoglu, Güzin
Abstract : Purpose: Prediction problems raised in uncertain environments require different solution approaches such as grey prediction models, which consider uncertainty in information and also enable the use of small data sets. The purpose of this paper is to investigate the comparative performances of grey prediction models (GM) and Markov chain integrated grey models in a demand prediction problem. Design/methodology/approach: The modeling process of grey models is initially described, and then an integrated model called the Grey-Markov model is presented for the convenience of applications. The analyses are conducted on a monthly demand prediction problem to demonstrate the modeling accuracies of the GM (1, 1), GM (2, 1), GM (1, 1)-Markov, and GM (2, 1)-Markov models. Findings: Numerical results reveal that the Grey-Markov model based on GM (2, 1) achieves better prediction performance than the other models. Practical implications: It is thought that the methodology and the findings of the study will be a significant reference for both academics and executives who struggle with similar demand prediction problems in their fields of interest. Originality/value: The novelty of this study comes from the fact that the GM (2, 1)-Markov model has been first used for demand prediction. Furthermore, the GM (2, 1)-Markov model represents a relatively new approach, and this is the second paper that addresses the GM (2, 1)-Markov model in any area.